2009
DOI: 10.1111/j.1365-2966.2009.15151.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale optical turbulence simulations at Dome C

Abstract: In recent years, ground-based astronomy has been looking towards Antarctica, especially its summits and the internal continental plateau, where the optical turbulence appears to be confined in a shallow layer close to the icy surface. Preliminary measurements have so far indicated rather good values for the seeing above 30-35 m: around 0.3 arcsec at Dome C. Site-testing campaigns are however extremely expensive; instruments provide only local measurements and atmospheric modelling might represent a step ahead … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 21 publications
6
47
0
Order By: Relevance
“…The atmospheric models have been used for the first time to reconstruct and characterize the C 2 N profiles by Masciadri, Vernin & Bougeault (1999a,b). Since then, much progress has been achieved by our group: the model has been applied to different astronomical sites in a simple monomodel configuration (Masciadri, Vernin & Bougeault 2001; Masciadri & Garfias 2001) and more recently in a grid‐nesting configuration (Lascaux et al 2009), a new calibration technique has been proposed (Masciadri & Jabouille 2001) and statistically validated (Masciadri, Avila & Sanchez 2004) and the first application of the Meso‐Nh model as a tool of turbulence characterization has been presented (Masciadri & Egner 2006). However, so far we could always access GS measurements concentrated in a well‐defined period of time.…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric models have been used for the first time to reconstruct and characterize the C 2 N profiles by Masciadri, Vernin & Bougeault (1999a,b). Since then, much progress has been achieved by our group: the model has been applied to different astronomical sites in a simple monomodel configuration (Masciadri, Vernin & Bougeault 2001; Masciadri & Garfias 2001) and more recently in a grid‐nesting configuration (Lascaux et al 2009), a new calibration technique has been proposed (Masciadri & Jabouille 2001) and statistically validated (Masciadri, Avila & Sanchez 2004) and the first application of the Meso‐Nh model as a tool of turbulence characterization has been presented (Masciadri & Egner 2006). However, so far we could always access GS measurements concentrated in a well‐defined period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the performance of the Antarctic Mesoscale Prediction System (described by Powers et al 2003) in retrieving surface temperature, Bromwich et al (2005) have shown that over the Antarctic plateau this model gives a positive bias of about 1 • C during the summer. Lascaux et al (2009), when comparing 47 radiosoundings temperature profiles collected at Dome C in the winter of 2005 with the results of a mesoscale model simulation, found substantial differences between experimental and model profiles in the first 200 m above the surface. Gallée and Gorodetskaya (2010) validated a limited area model over Dome C during the cold season.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in recent years, the optical turbulence over the Antarctic plateau has been the subject of studies by astronomers (e.g. Aristidi et al 2005a,b;Geissler and Masciadri 2006;Hagelin et al 2008;Trinquet et al 2008;Lascaux et al 2009). As shown by e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2006). More recently, it has been statistically validated above Dome C by Lascaux et al (2009Lascaux et al ( , 2010. The most important results obtained in these last papers are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 87%
“…4 For this study, therefore, the RAMP Digital Elevation Model has been used. The orography of each area of interest in this study (Dome C, Dome A, South Pole) is displayed on Fig.…”
Section: Numerical Set-upmentioning
confidence: 99%